Identifying Tourism Attractions’ Potentials of Protected Area: A Case Study in Bulue Village, Soppeng District, Indonesia - Eko Yuwono; Risma Illa Maulany; Roland A. Barkey (Journal of Indonesian Tourism and Development Studies, 2020)
The purpose of this study was to identify the tourism attractions’ potentials of the landscape that had the major function as protected areas. Bulue Village was selected in this study as nearly 85% of the territory lies inside the protected areas. The comprehensive spatial analysis combined with descriptive analysis was utilized as approaches toward the study. The Scenic Beauty Estimation (SBE) was also carried out to obtain the potential of nature-based tourism attractions based on tourist’s perceptions. The results showed that there were nine spots of attractions that had a high value of SBE. Those attractions were identified as Lejja hot spring (SBE=81.33), Lejja view (SBE=129.33), camping ground (SBE=51.78), Datae hot spring (SBE=71.22), Menawoe waterfall (SBE=184.44), Lapaserengi waterfall (SBE=143.00), Batumurue waterfall (SBE=127.89), Waepuange waterfall (SBE=122.11), and Sarasa-tandre waterfall (SBE=147.44). Only Anoa sanctuary has a moderate value. Nevertheless, there some issues that need to be considered, in particular, to prevent further forest degradation by providing economic alternatives for the locals and improving the management of the site. These findings have shown the need for finding a specific strategy to develop ecotourism activities based on the characteristics of the landscape.Keywords: Bulue village, ecotourism in protected area, landscape-based ecotourism, scenic beauty estimation.